Tracing pathways: exploring sense of place through metaphor and material : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Ronald, Penny (Massey University, 2018)
This research project seeks to highlight local textile production by exploring the concept of place in the context of design practice. Focusing on the farm in Southland where I am from, weaving has been used as a metaphor in order to interpret the place conceptually as well as materially through using natural colorants and wool from New Zealand. Notions of thinking through making have informed my design methodology, using the process of developing iterations of different drawings and designs to influence the resolve of the final outcome. The research celebrates residue of process, showing the constraints of what my physical body was able to weave in relation to the immensity of the farm landscape. I have contextualized my final outcome of a woven pathway within the framework and principles of slow design, developing a provocation which aims to create discussion around localism and slow textile processes such as natural dye and weave. As is the goal of all slow design, the overarching aim is to contribute to the shift towards sustainability, with the suggestion that this project could be expanded to include different localities, or to influence designs of a commercial nature. At the heart of this project is my passion for New Zealand wool. This is the key driver for my exploration and the material that is used throughout this project. I intend to highlight connections between the crossbred wool industry and localism by delving deeper into my family’s farm where wool is grown. Through slow design, I intend to provoke the viewer to consider more holistically the connection between wool, and the area which it originates from. The 'thinking through making' framework has allowed me to authentically approach this research project as a journey, revealing the many layers of the farm and new pathways that have emerged as the project developed. I have chosen to order this exposition accordingly, describing new layers of research and design iterations as they have developed and then bringing the research together by examining slow design principles and localism.
Keywords: Textile crafts; Design; Woolen and worsted weaving; Landscape; Farm life; New Zealand; Southland District; Place (Philosophy) in art